Coexistence of two structurally similar but functionally different PII proteins in Azospirillum brasilense. - de Zamaroczy, M (1996)
The coexistence of two different PII, proteins in Azospirillum brasilense was established by comparing proteins synthesized by the wild-type strain and two null mutants of the characterized glnB gene (encoding PII) adjacent to glnA. Strains were grown under conditions of nitrogen limitation or nitrogen excess. The proteins were analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) or isoelectric focusing gel electrophoresis and revealed either by [32P]phosphate or [3H]uracil labeling or by cross-reaction with an anti-A. brasilense PII-antiserum. After SDS-PAGE, a single band of 12.5 kDa revealed by the antiserum in all conditions tested was resolved by isoelectric focusing electrophoresis into two bands in the wild-type strain, one of which was absent in the glnB null mutant strains. The second PII protein, named Pz, was uridylylated under conditions of nitrogen limitation. The amino acid sequence deduced from the nucleotide sequence of the corresponding structural gene, called glnZ, is very similar to that of PII. Null mutants in glnB were impaired in regulation of nitrogen fixation and in their swarming properties but not in glutamine synthetase adenylylation. No glnZ mutant is yet available, but it is clear that PII and Pz are not functionally equivalent, since glnB null mutant strains exhibit phenotypic characters. The two proteins are probably involved in different regulatory steps of the nitrogen metabolism in A. brasilense.